PEMANFAATAN E-COMMERCE MODEL BUSINESS TO CONSUMER PADA PUTRI TAPIS LAMPUNG - Auliya Rahman Isnain; Muhammad Indigo; Adhie Thyo Priandika (Universitas Teknokrat Indonesia, 2023)
This study aims to build an E-Commerce system based on the Business to Consumer website model, in order to increase sales at Putri Tapis Lampung and make it easier to check stock in the Warehouse using the Extreme Programming method. The results of the test calculations that have been carried out using black box testing have not found any errors or bugs in each application's functional testing process. practical and useful to the public) and hedonic qualities (perceptions of pleasurable qualities). Utilization of the E-commerce business-to-consumer model for Putri Tapis Lampung, built using the Laravel framework, and the method used is extreme programming and testing is carried out using black box testing and UEQ (User Experience Questionnaire).